2022
DOI: 10.1002/aoc.6600
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural elucidation, and density functional theory investigation of new mononuclear Fe(III), Ni(II), and Cu(II) mixed‐ligand complexes: Biological and catalase mimicking activity exploration

Abstract: The present paper deals with synthesis new mononuclear 1:1:1 metal:ligand:co‐ligand complexes, FeLG, NiLG, and CuLG, where L = 1‐{(E)‐[(4‐methylphenyl)imino]methyl}‐2‐naphthol and G = Glycine. The synthesized complexes were characterized based on elemental analysis, Fourier transform infrared spectroscopy (FT‐IR), ultraviolet–visible (UV–vis), mass spectra, molar conductance, magnetic susceptibility, and thermal analysis (TGA) in addition to stoichiometry determination via molar ratio method. The isolated meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It was shown that the activity of the complexes increased with the strength of the bond between the metal and ligand, the size of the cation, the number of receptor sites, the rate of diffusion, and the combined action of the metal and ligand to inactivate the biomolecules [ 35 ]. In addition, the IZ values for the specified compounds were compared to those of the antibiotic Chloramphenicol, which indicates a high activity index (%), Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the activity of the complexes increased with the strength of the bond between the metal and ligand, the size of the cation, the number of receptor sites, the rate of diffusion, and the combined action of the metal and ligand to inactivate the biomolecules [ 35 ]. In addition, the IZ values for the specified compounds were compared to those of the antibiotic Chloramphenicol, which indicates a high activity index (%), Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The MOE program was used to undertake a molecular docking investigation of the subject chemicals analogues against the cyclooxygenase (COX) enzyme. 47…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Electrophilic and nucleophilic reactivity are represented by the blue and red MEP areas, respectively. 47 The optimized geometry's MEP diagram is mapped up at the same level of theory as the examined compounds, as shown in Figure 3. Because of their electronrich environment, the red patches around hetero atoms (O, N, Cl, and S) in the subject substrates are ideal targets for electrophilic assault.…”
Section: Molecular Electrostatic Potential (Mep)mentioning
confidence: 99%
“…Molecular docking investigation was performed in order to identify the binding interactions of titled molecules and their orientations within the active site of the target protein. In this study, molecular docking was performed on E. coli FabH-CoA complex (PDB ID: 1HNJ) using MOE [26][27][28]. FabH is involved in the biosynthesis of fatty acids and considered the targeted receptor for knowing the molecules' potential as antimicrobial candidates [29,30].…”
Section: Molecular Dockingmentioning
confidence: 99%